Flexural response of ferrocement I-beam to third-point loading - Acma, Leoncio Mariano C. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2017)
This study aimed to determine the flexural response of ferrocement I-Beam to third-point loading. Three replicates for each test specimen were made. They were cast using the fabricated C-shaped formwork reinforced with 16, 18, 20, and 22 layers of wire mesh reinforcement then installed back-to-back and connected with A-325 bolts to form I-shaped beams. The said beams were subjected to third-point load test using the Universal Testing Machine. An empirical equation for the determination of flexural strength of the form fr (x) =732.19 + 131.18x was developed. There was a positive response to the number of layers of wire mesh to the ferrocement I-Beam. By converting the number of layers to the volume fraction of reinforcement from the results of Acma (2014) and Acma et al. (2015), a correlation of the studies was made resulting to an empirical equation. The cracking behavior at failure show perceptible, multiple cracks at each of the three replicates but the time=load curve diagram shows a proportional slope implying that the ferrocement I-beam has exhibited the ductile behavior required; the increase in the number of layers of wire mesh reinforcement also made a positive response to the flexural strength of the ferrocement I-beam.